2015
DOI: 10.1149/2.0941504jes
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of In Situ Gas Evolution during High Voltage Formation in Li-Ion Pouch Cells

Abstract: Li-ion pouch cells were made to study the factors that influence gas evolution during formation (first charge). Electrode materials, electrolyte additives and temperature were varied. Measurements were made using the Archimedes' In Situ Gas Analyzer at Dalhousie University. When cells are charged to high voltages (>4.2 V) there is gas evolution, presumed to be from reactions on the surface of the positive electrode. This is separate from the gas evolution known to happen at lower voltage (<3.5 V) caused by rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 41 publications
6
86
1
Order By: Relevance
“…After degassing, they were charged to 4.5 V and held for 1 h and then degassed again (the second degassing step). These degassing voltages were selected based on the in-situ gas measurements, which indicated that most of the gas was produced during the first cycle at voltages below 3.5 V and 4.3 V. 37 After the two degassing steps, cells were discharged to 3.8 V, held for 5 h and cell impedance was then measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After degassing, they were charged to 4.5 V and held for 1 h and then degassed again (the second degassing step). These degassing voltages were selected based on the in-situ gas measurements, which indicated that most of the gas was produced during the first cycle at voltages below 3.5 V and 4.3 V. 37 After the two degassing steps, cells were discharged to 3.8 V, held for 5 h and cell impedance was then measured.…”
Section: Methodsmentioning
confidence: 99%
“…After degassing, they were charged to 4.5 V and held for 1 h and then degassed again (the second degassing step). These degassing voltages were selected based on the in-situ gas measurements, which indicated that most of the gas was produced during the first cycle at voltages below 3.5 V and 4.3 V. 37 After the two degassing steps, cells were discharged to 3.8 V, held for 5 h and cell impedance was then measured.Storage experiments.-After cell impedance measurements, the cells with X_E_VC_TTSPi and X_EE_VC_TTSPi were discharged to 2.8 V and charged back to 4.5 V at C/20 and held at 4.5 V for 30 hours. They were then moved to a storage system and stored at 40 or …”
mentioning
confidence: 99%
“…Details of the Archimedes volume measurement instruments at Dalhousie University can be found in several publications. 1,9,10 Quantification and identification of gases using GC-TCD.-Quantification and identification of the gases inside lithium-ion cells were done using a gas chromatograph (GC, Bruker 436-GC) and a thermal conductivity detector (TCD, Bruker). The instrumentation, detector calibration, sample preparation and analysis methods were the same used by Petibon et al 11 Lithium-ion cells were placed in an air-tight gas extraction device (GED).…”
mentioning
confidence: 99%
“…Some of this gas is then consumed by reduction on the negative electrode (e.g., reduction of CO 2 to oxalate). 15,17 It has been shown that for given electrolyte, additives and electrode pairs, an increase in temperature causes gas evolution to occur at lower voltages and the total amount of gas generated to increase significantly.Xia et al 16 investigated formation, cycling and storage of graphite/NMC pouch cells (cells balanced for a 2.8-4.2 V voltage window) with different electrolyte additives and observed that the volume of gas generated during the formation cycles (up to ∼13 mL Ah −1 ) was roughly correlated to the amount of irreversible capacity loss. This implied that the additives affected the amount of irreversible capacity loss and gas formation similarly.…”
mentioning
confidence: 99%